Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/admt.202101633
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Biohybrid Microsystems

Abstract: are not able to fully meet the challenges related to the creation of such systems. A number of methods are known that make it possible to form 3D structures, for example, Rolling-Up technology and imprint lithography. [1][2][3][4] However, a rather short list of materials that can be used in such technologies and a too narrow range of 3D shapes that can be fabricated using these methods seriously limit the application fields of the techniques. It seems that additive manufacturing (AM) technology, or 3D printin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 384 publications
(593 reference statements)
0
3
0
Order By: Relevance
“…While these chips are mainly fabricated on PDMS, inherent complexities arise during its fabrication and require extra steps to alleviate the same. The combination of microfluidics and 3D printing for organ-on-chip applications is efficient for fabricating complex flow channels and provides the feasibility of creating biological structures with 3D cell distributions [383][384][385][386][387].…”
Section: Limitations and Future Considerations For Single Rbc Trappin...mentioning
confidence: 99%
“…While these chips are mainly fabricated on PDMS, inherent complexities arise during its fabrication and require extra steps to alleviate the same. The combination of microfluidics and 3D printing for organ-on-chip applications is efficient for fabricating complex flow channels and provides the feasibility of creating biological structures with 3D cell distributions [383][384][385][386][387].…”
Section: Limitations and Future Considerations For Single Rbc Trappin...mentioning
confidence: 99%
“…For instance, researchers have used 3D printing to create microelectrodes/nanoelectrodes with various shapes and sizes and tested their performance in detecting dopamine release in live brain tissue . The results showed that the 3D-printed microelectrodes could detect dopamine signals with high sensitivity and selectivity, providing a powerful tool for studying the mechanisms of PD and other related disorders. , Similarly, researchers have developed a 3D-printed microelectrode array for high-resolution mapping of epileptic activity in mice brains. The array consisted of 16 independently addressable microelectrodes with a total size of less than 1 mm 2 and could detect submillisecond changes in neural activity.…”
Section: Prospects Of 3d-printed Microelectrodes In Diagnosismentioning
confidence: 99%
“…The coupling of materials to living cells is a coveted topic in biomedical engineering, with potential applications in the localized delivery of therapeutic or immunosuppressive drugs, cell and tissue transplantation, and cell therapy. [33][34][35][36] Furthermore, exploring the unique microenvironment of the ACE as a transplantation site for biohybrid structures is crucial in shaping a general concept in the field.…”
Section: Introductionmentioning
confidence: 99%